THE PERFORMANCE INDEX OF PRIVATE AND PUBLIC SECTOR HOSPITALS OF KARACHI, PAKISTAN - Khan, Najm Us Saqib; Hafeez, Assad; Qamar, Khadija; Tasawar, Amna; Hisammuddin, Effat; Bukhari, Ashfaq Ahmad Shah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the performance index of private and public sector hospitals of Karachi, Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: In a tertiary care hospitals (one private and one public sector) of Karachi, from Nov 2016 to Nov 2017.Methodology: A sample size of 153 were enrolled by purposive sampling technique. Performance index of both hospitals was compared by asking questions from the hospitals staff. Data were collected by the researcher using closed ended questionnaire.Results: Out of 153, 78 (51%) cases were for private hospitals and 75 (49%) cases were for public hospitals. While evaluating the performance index by hospital work area/unit elements, “Enough staff to handle workload" was significantly higher for private hospitals with the p-value of